Preparation method of polyurethane foam buffer material based on FIAM factor

By introducing FIAM factors into polyurethane foam materials, building boron oxygen coordination enhancement structure and adjusting isocyanate components, the problems of insufficient protection ability and unstable foaming under high strain rate impact are solved, and excellent buffering energy absorption performance and adaptive adjustment performance are achieved.

CN120484216APending Publication Date: 2025-08-15BEIJING ZHONGKE LIXIN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510777610.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

The existing polyurethane foam materials have insufficient impact energy absorption capacity, lack of adaptive response mechanism, and poor compatibility of functional fillers with foaming systems, resulting in insufficient protection capacity and unstable foaming process under high strain rates or instantaneous impact.

Method used

By introducing FIAM factors, a boron-oxygen coordination enhancement structure is constructed, multiple response behaviors such as shear hardening, structural tackification and modulus transition are realized, and through quantitative correction strategies of isocyanate components, NCO/OH reaction balance is ensured and the material's coordinated energy absorption and adaptive adjustment functions are enhanced.

Benefits of technology

While maintaining lightweight flexibility, the impact response capability and foam forming stability are significantly improved. The peak impact force of the optimized polyurethane foam material is reduced by 50%-70% at the same thickness, and has excellent adaptive buffering ability and stable process forming.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120484216A_ABST
    Figure CN120484216A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a polyurethane foam buffer material based on an FIAM factor. The preparation method comprises the following steps: (1) preparing the FIAM factor; (2) introducing and dispersing an FIAM factor; and (3) introducing a component A for generating a polyurethane foam raw material, and foaming to obtain the polyurethane foam buffer material based on the FIAM factor. The material has the following beneficial effects: (1) the material has excellent buffering and energy-absorbing performance; (2) excellent synergistic energy absorption and modulus self-adaptive adjustment performance; and (3) the process formability is stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of polymer materials and science, and in particular to a method for preparing a polyurethane foam cushioning material based on FIAM factors. Background Art

[0002] As a typical porous cushioning medium, polyurethane foam is widely used in consumer electronics packaging, precision instrument transportation, protective equipment manufacturing, and aerospace applications. Its advantages include lightweight, flexible molding processes, excellent cushioning properties, and strong structural controllability. It has become a common cushioning material in high-value cargo transportation and impact protection applications.

[0003] The cushioning mechanism of traditional polyurethane foam relies primarily on the elastic deformation of its skeleton structure and pore compression to absorb external impact energy. However, polyurethane foam cushioning systems still have the following key flaws and shortcomings in terms of performance and processing.

[0004] (1) Insufficient buffering and energy absorption performance: The buffering performance of traditional polyurethane foam mainly relies on pore structure compression and skeleton elastic deformation to dissipate impact energy. Under high strain rate or instantaneous impact load, this type of foam material is prone to problems such as local structural collapse, rebound hysteresis, and high impact force peak. It is difficult to achieve effective attenuation and slow release of short-term high-intensity impact, which affects its ability to protect precision devices.

[0005] (2) Single buffer mechanism, lack of synergistic energy absorption and adaptive control capabilities: Existing polyurethane foams are mostly based on static mechanics design, and their energy absorption mechanism is mainly compression deformation, which does not effectively integrate multiple energy dissipation mechanisms such as impact hardening, viscoelastic transition, and instantaneous rearrangement of molecular structure. Under complex dynamic working conditions, the material cannot automatically adjust the modulus and response behavior according to the impact rate, resulting in slow response under light loads and insufficient protection under heavy loads. There are problems of "inefficient response" or "oversaturated energy absorption", and the overall impact resistance has limited room for improvement.

[0006] (3) Poor compatibility of functional fillers, which can easily induce defoaming and collapse: Impact-responsive materials such as STF / STG usually have high viscosity or a colloidal form, and are prone to problems such as poor physical compatibility, uneven dispersion, and poor interfacial wettability with polyurethane base materials. During the foaming process, if the ratio of the reaction components is not corrected in a timely manner, especially if the ratio of isocyanate to hydroxyl components is unbalanced, the gel time will be prolonged, the foaming process will be unstable, and defects such as defoaming, collapse, and foam wall rupture will easily occur, thereby affecting the integrity and cushioning performance of the molded foam. Summary of the Invention

[0007] Purpose of the invention: In view of the shortcomings of the existing technology (the existing polyurethane foam materials have insufficient impact energy absorption capacity, lack of adaptive response mechanism, and poor compatibility between functional fillers and foaming systems), the present invention discloses a preparation method of a polyurethane foam cushioning material based on the FIAM (Flexible Intelligent Anti-impact Material) factor.

[0008] This method constructs a FIAM functional factor system with a boron-oxygen coordination enhanced structure, so that it can trigger multiple response behaviors such as shear hardening, structural viscosity enhancement and modulus transition when subjected to external impact or high strain rate load.

[0009] On the one hand, the FIAM factor can provide rate-sensitive local stress support at the microscale, and on the other hand, it can form a synergistic network with the polyurethane foam matrix at the macroscale, enhance the interfacial bonding strength, and realize the overall synergistic energy absorption and stiffness self-regulation function of the material.

[0010] Furthermore, to address the potential dilution of reactive components caused by traditional functional fillers, this invention further utilizes a quantitative correction strategy for the isocyanate component to precisely adjust the A / B ratio, ensuring a balanced NCO / OH reaction and significantly reducing the risks of defoaming, collapse, and structural incompleteness associated with prolonged gel time. This method enables polyurethane foam to maintain its lightweight and flexible properties while achieving excellent impact responsiveness and foaming stability, meeting the performance requirements of high-end cushioning packaging, protective materials, and vibration reduction applications.

[0011] A method for preparing a polyurethane foam cushioning material based on FIAM factors, comprising the following steps:

[0012] (1) Preparation of FIAM factor;

[0013] (2) Introduction and dispersion of FIAM factors;

[0014] (3) The A component of the polyurethane foam raw material is introduced, and after the foaming is completed, the polyurethane foam cushioning material based on the FIAM factor (FIAM-PUF) is obtained.

[0015] Furthermore, in parts by mass, the specific steps of step (1) are as follows:

[0016] (11) Preparation of STG (shear thickening gel) precursor:

[0017] The boron-containing raw material and hydroxyl-terminated polydimethylsiloxane (PDMS) are mixed by hot melt and continuously stirred at a speed of at least 500 rpm to cause a borate esterification reaction to form an STG precursor having a polyborosiloxane network with a low degree of crosslinking, wherein:

[0018] The mass ratio of the added boron-containing raw material to the hydroxyl-terminated polydimethylsiloxane is (2-6):100;

[0019] (12) adding 30 to 40 parts of the STG precursor obtained in step (11) and 10 to 15 parts of a boron-oxygen coordination enhancer to 50 parts of dimethyl silicone oil, and then stirring the mixture in a water bath at a constant temperature of at least 80° C. using a magnetic stirrer at at least 150 rpm for at least 3 hours to obtain an intermediate product;

[0020] (13) Nanoparticle enhancement

[0021] After the intermediate product obtained in step (12) is cooled to room temperature, nano-scale fumed silica is slowly added in small amounts and multiple times, and stirred at a high speed of at least 2000 rpm to form a stable high-viscosity FIAM factor.

[0022] FIAM materials exhibit a viscous flow state at room temperature, containing both BO dynamic crosslinks and triboroxane rings. This allows for a rapid increase in modulus under high-speed shear or impact. FIAM materials exhibit low modulus and viscous flow behavior at low impact rates. However, when the shear or impact rate exceeds a critical value, the molecular segments or microparticle clusters containing the BO dynamic crosslinks rapidly rearrange, significantly increasing the storage modulus and macroscopic viscosity, thus exhibiting an impact hardening effect.

[0023] Furthermore, the boron-containing raw material in step (11) is one or more of boric acid, phenylboric acid, and diphenylboric acid.

[0024] Furthermore, the reaction temperature of the borate esterification reaction in step (11) is 140-150° C., and the reaction time is 4-5 h.

[0025] Furthermore, the boron-oxygen coordination enhancer in step (12) is one or more of phenylboric acid and diphenylboric acid.

[0026] Furthermore, the viscosity of the dimethyl silicone oil in step (12) is 20 to 100 cSt.

[0027] Furthermore, in step (13), the addition ratio of the nano-scale fumed silica is 5% to 20% based on the total mass of the intermediate product;

[0028] The particle size of the nano-scale fumed silica is 10 to 30 nm.

[0029] Furthermore, in parts by mass, the specific steps of step (2) are as follows:

[0030] (21) The FIAM factor obtained in step (1) is added to 8 parts of the B component of the polyurethane foam raw material to form a FIAM-B component, wherein:

[0031] Based on the total mass of the B component of the polyurethane foam raw material, the FIAM factor is added in an amount of 2 wt% to 10 wt%;

[0032] The B component of the polyurethane foam raw material is composed of polyether polyol and stabilizer, wherein:

[0033] The mass ratio of polyether polyol to stabilizer is 100:(0.4-0.6);

[0034] (22) Stirring the FIAM-B component obtained in step (21) at a rate of 300-500 rpm for at least 10 minutes, and then proceeding to step (23);

[0035] (23) The FIAM-B component stirred in step (22) is subjected to ultrasonic dispersion treatment at room temperature at a power of 100 to 300 W for at least 20 minutes to obtain the FIAM-B component.

[0036] Furthermore, the stabilizer in step (21) is one or more of L-580 polymerized siloxane stabilizer, methylcyclohexylamine, and ethylene glycol monoallyl ether.

[0037] Furthermore, in parts by mass, the specific steps of step (3) are as follows:

[0038] (31) adding an appropriate amount of component A for generating a polyurethane foam raw material to the FIAM-B component obtained in step (2), quickly mixing and stirring to obtain a mixture;

[0039] (32) The mixture obtained in step (31) is immediately injected into a mold or placed in an open space for free foaming. After the foaming is completed, a polyurethane foam cushioning material (FIAM-PUF) based on the FIAM factor is obtained.

[0040] Furthermore, component A of the polyurethane foam raw material generated in step (31) is isocyanate.

[0041] Furthermore, the isocyanate is one of 4,4'-diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), and naphthalene diisocyanate (NDI).

[0042] Furthermore, in step (31):

[0043] If the addition ratio of the FIAM factor is 2 wt% to 4 wt%, the addition amount of component A for generating the polyurethane foam raw material in step (31) is 10.2 to 10.5 parts;

[0044] If the addition ratio of the FIAM factor is 4 wt% to 6 wt%, the addition amount of component A for generating the polyurethane foam raw material in step (31) is 10.5 to 10.8 parts;

[0045] If the addition ratio of the FIAM factor is 6 wt% to 10 wt%, the addition amount of component A for generating the polyurethane foam raw material in step (31) is 10.8 to 11.2 parts.

[0046] Furthermore, in step (31), the stirring speed is 1000-1500 rpm, and the stirring time is 5-10 seconds.

[0047] Furthermore, in step (32), the foaming temperature is controlled at 25 to 60° C., and the foaming time is controlled at 10 to 60 seconds.

[0048] Beneficial effects: The method for preparing a polyurethane foam cushioning material based on FIAM factor disclosed in the present invention has the following beneficial effects:

[0049] (1) Excellent buffering and energy absorption performance: FIAM factors cross-link with the skeleton by filling pores, wrapping the skeleton, and attaching particles. Under impact conditions, they rapidly dissipate large amounts of energy through their own impact hardening effect and the synergistic deformation between multiphase materials, effectively absorbing impact kinetic energy. Their instantaneous increase in stiffness limits excessive deformation of the foam, thereby suppressing the occurrence of bottoming out. At the same time, the increase in the foam's platform stress improves deformation energy absorption performance, significantly attenuating the peak impact force transmitted to the protected object and providing excellent buffering and protection. Under the same buffer material thickness and impact conditions, the optimized FIAM-PUF reduces the peak impact transmission force by 50% to 70% compared to the unoptimized PUF.

[0050] (2) Excellent synergistic energy absorption and modulus adaptive adjustment performance: After the FIAM factor is introduced into the polyurethane matrix, the BO dynamic cross-linking network and the nanoparticle synergistic deformation network formed undergo instantaneous rearrangement of the network structure and aggregation and interlocking of the molecular chains when subjected to high-speed shear or impact, showing impact hardening characteristics, realizing the modulus transformation and response adjustment function of the material at different impact rates, and having excellent adaptive buffering capacity.

[0051] (3) Stable process formability: By rationally introducing FIAM into component B, combined with ultrasonic dispersion and isocyanate ratio correction strategies, the defoaming interference caused by functional fillers is overcome, the defoaming rate is greatly reduced, the foam structure is complete, the pores are uniform, and the foaming process is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The present invention discloses a flow chart of a method for preparing a polyurethane foam cushioning material based on FIAM factors.

[0053] Figure 2 Schematic diagram of the impact transmission force curves of the FIAM-PUF polyurethane foam cushioning material based on the FIAM factor prepared in Example 1 and the polyurethane foam sample PUF prepared in the control example.

[0054] Figure 3 Schematic diagram of the corresponding relationship between the elastic modulus and strain rate of the polyurethane foam cushioning material based on the FIAM factor prepared in Example 1. DETAILED DESCRIPTION

[0055] The specific embodiments of the present invention are described in detail below.

[0056] The "ranges" disclosed herein are defined in the form of lower and upper limits. A given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive and can be combined arbitrarily, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 10 to 50 is listed for a particular parameter, it is understood that ranges of 10 to 40 and 20 to 50 are also contemplated. Furthermore, if the minimum range values listed are 1 and 2, and if the maximum range values listed are 3, 4, and 5, then the following ranges are all contemplated: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4, and 2 to 5. In this application, unless otherwise specified, the numerical range "a to b" is an abbreviation for any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0 to 5" means that all real numbers between "0 to 5" are listed herein, and "0 to 5" is simply an abbreviation for these numerical combinations.

[0057] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0058] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0059] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0060] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0061] Unless otherwise specified, the reaction is carried out at room temperature and pressure.

[0062] Unless otherwise specified, all parts or percentages are by weight.

[0063] In the present invention, all substances used are known substances and can be purchased or synthesized by known methods.

[0064] In the present invention, the devices or equipment used are all conventional devices or equipment known in the art and are commercially available.

[0065] The present invention uses the following test method to evaluate the cushioning performance of foam:

[0066] ① Drop hammer impact test: Referring to "GB / T 8167-2008 Dynamic Compression Test Method for Packaging Cushioning Materials," the peak transmission force of polyurethane foam (PUF) materials under different energy levels was measured. The cushioning performance of the polyurethane foam before and after FIAM factor optimization was compared. The reduction rate of the peak transmission force of the optimized FIAM-PUF material relative to the unoptimized PUF material was calculated to evaluate the optimization effect of the FIAM factor.

[0067] ② Static / dynamic compression test: Using a universal materials testing machine and a split Hopkinson bar tester, the static / dynamic stress-strain curves of the FIAM-PUF material were measured. The relationship between its elastic modulus and strain rate was analyzed, and the strain rate effect of the material's elastic modulus was evaluated to verify the FIAM-PUF material's ability to adaptively adjust its modulus with impact rate.

[0068] ③ Defoaming behavior monitoring: The defoaming behavior of the molded FIAM-PUF was monitored by static observation. The apparent volume was measured after standing at room temperature for 48 hours, and the shrinkage rate relative to the volume at the time of demolding was calculated as the defoaming rate parameter (η). The defoaming rate parameters of the FIAM-PUF before and after the adjustment of component A were compared to analyze the effect of the process adjustment.

[0069] Comparison example:

[0070] The preparation method of polyurethane foam cushioning material (PUF) comprises the following steps:

[0071] (1) Prepare polyurethane foam raw materials

[0072] A two-component polyurethane foam system is used, wherein:

[0073] Component A (black material): 4,4'-diphenylmethane diisocyanate (MDI);

[0074] Component B (white material): composed of polyether polyol and methylcyclohexylamine (stabilizer), and the mass ratio of polyether polyol to methylcyclohexylamine is 100:0.5;

[0075] The preferred mass ratio of component A to component B is 105:84.5.

[0076] (2) Mix the above-mentioned component A and component B quickly and evenly according to the above-mentioned proportions to obtain a mixture;

[0077] (3) The obtained mixture is immediately injected into a mold or placed in an open space for free foaming at 40°C for 50 seconds. After completion, a polyurethane foam cushioning material (PUF) is obtained.

[0078] The prepared polyurethane foam cushioning material (PUF) was tested for performance according to the above method, and the results are as follows:

[0079] Density range is 0.01~0.2g / cm 3 , pore diameter 0.02~2mm, porosity 70%~95%, elastic modulus 0.03~3MPa.

[0080] Example 1: Preparation and performance evaluation of polyurethane foam with 2.5 wt% FIAM factor addition

[0081] A method for preparing a polyurethane foam cushioning material based on FIAM factors, comprising the following steps:

[0082] (1) Preparation of FIAM factor:

[0083] 6 g of boric acid and 200 g of hydroxyl-terminated polydimethylsiloxane (PDMS) were hot-melt mixed and stirred at 145°C and 500 rpm for 4.5 hours to allow borate esterification to occur, generating a STG precursor with a low-crosslinked polyborosiloxane network.

[0084] 30 g of the STG precursor (primarily polyborosiloxane) prepared in the above steps and 10 g of phenylboric acid were added to 50 g of dimethyl silicone oil with a viscosity of 50 cSt. The mixture was magnetically stirred at 150 rpm in an 80°C constant temperature water bath for 3 hours to promote the formation of the BO-Si coordination structure. After cooling to room temperature, 10 g of nano-fumed silica (particle size approximately 20 nm) was gradually added and stirred at high speed (2000 rpm) for 5 minutes to prepare the FIAM factor.

[0085] (2) Introduction and dispersion of FIAM factors:

[0086] 4.5 g of FIAM factor was added to 80 g of the B component of the polyurethane foam raw material, stirred for 10 minutes, and then ultrasonically treated at 200 W power for 20 minutes to form 84.5 g of FIAM-B component, wherein:

[0087] The component B of the polyurethane foam raw material is composed of polyether polyol and stabilizer, and the mass ratio of polyether polyol to stabilizer is 100:0.5; the stabilizer is methylcyclohexylamine;

[0088] (3) Introduction of component A for generating polyurethane foam raw materials

[0089] 105 g of component A (MDI) and FIAM-B, the raw material for generating polyurethane foam, were quickly mixed (stirred at 1500 rpm for 8 seconds) in a mass ratio of 105:84.5, immediately injected into a mold, and allowed to foam freely at 25°C for about 30 seconds to obtain a polyurethane foam cushioning material (FIAM-PUF) based on the FIAM factor.

[0090] Sample performance evaluation

[0091] According to the performance test requirements, the molded foam material is cut into samples of sizes such as 100mm×100mm×60mm (drop hammer impact sample), Φ15mm×8mm (static / dynamic compression sample), and 100mm×100mm×100mm (defoaming rate sample).

[0092] Drop weight impact test: Figure 2 Schematic diagram of the impact transmission force curve of the polyurethane foam cushioning material FIAM-PUF based on FIAM factor prepared in Example 1 and the polyurethane foam sample PUF prepared in the control example, as shown in FIG. Figure 2As shown in the figure, under an impact energy of 10J, the peak impact transmission force of the FIAM-PUF polyurethane foam cushioning material based on the FIAM factor prepared in Example 1 is 0.35kN, while the peak impact transmission force of the polyurethane foam sample PUF prepared in the control example is 0.84kN. The impact force transmission peak of FIAM-PUF is reduced by 58.3% relative to that of PUF material.

[0093] Static / dynamic compression test: within 0.001s -1 , 0.01s -1 , 700s -1 , 1600s -1 , 3000s -1 The elastic moduli under strain rate conditions are 0.18MPa, 0.20MPa, 0.25MPa, 0.32MPa and 0.41MPa respectively. The scatter plot of the modulus changing with strain rate is shown in the attached figure. Figure 3 Its modulus shows a significant strain rate enhancement effect, and the material has the function of adaptive adjustment according to the external load rate.

[0094] Defoaming rate parameter (η): After standing at room temperature for 48 hours after molding, the apparent volume shrinkage of the FIAM-PUF polyurethane foam cushioning material based on the FIAM factor prepared in Example 1 was measured to be approximately 2.1%, which was significantly lower than the 31.2% of the uncorrected system, indicating that the process solves the defoaming interference problem and the material molding is stable.

[0095] Example 2: Preparation and performance evaluation of polyurethane foam with 5 wt% FIAM factor addition

[0096] A method for preparing a polyurethane foam cushioning material based on FIAM factors, comprising the following steps:

[0097] (1) Preparation of FIAM factor:

[0098] 6 g of boric acid and 200 g of hydroxyl-terminated polydimethylsiloxane (PDMS) were hot-melt mixed and stirred at 145°C and 500 rpm for 4.5 hours to allow borate esterification to occur, generating a STG precursor with a low-crosslinked polyborosiloxane network.

[0099] 35g of STG precursor and 15g of phenylboric acid were added to 50g of dimethyl silicone oil with a viscosity of 50cSt, and magnetically stirred at 150rpm in a constant temperature water bath at 80°C for 3 hours. After cooling, 20g of nano-fumed silica (particle size 15-30nm) was added slowly in five times, with high-speed stirring (2000rpm) for 5 minutes each time to form a high-viscosity FIAM factor.

[0100] (2) Introduction and dispersion of FIAM factors

[0101] 9 g of FIAM factor was added to 80 g of the B component of the polyurethane foam raw material, stirred for 10 minutes, and then ultrasonically treated at 200 W power for 20 minutes to form 89 g of FIAM-B component, wherein:

[0102] The component B of the polyurethane foam raw material is composed of polyether polyol and stabilizer, and the mass ratio of polyether polyol to stabilizer is 100:0.5; the stabilizer is methylcyclohexylamine;

[0103] (3) Introduction of component A for forming polyurethane foam raw materials:

[0104] 112 g of component A (MDI) and FIAM-B, the raw material for generating polyurethane foam, were quickly mixed (stirring at 1500 rpm for 8 seconds) in a mass ratio of 112:89, immediately injected into a mold, and allowed to foam freely at 25°C for about 30 seconds to obtain a polyurethane foam cushioning material (FIAM-PUF) based on the FIAM factor.

[0105] Sample performance evaluation

[0106] According to the performance test requirements, the molded foam material is cut into samples of sizes such as 100mm×100mm×60mm (drop hammer impact sample), Φ15mm×8mm (static / dynamic compression sample), and 100mm×100mm×100mm (defoaming rate sample).

[0107] Drop hammer impact test: Under an impact energy of 3J, the peak impact transmission force of the FIAM-PUF polyurethane foam cushioning material based on the FIAM factor prepared in Example 2 was 0.31kN, while the peak impact transmission force of the polyurethane foam sample PUF prepared in the control example was 0.14kN. The impact force transmission peak of FIAM-PUF was reduced by 54.8% compared with that of PUF material.

[0108] Static / dynamic compression test: within 0.001s -1 , 0.01s -1 , 700s -1 , 1600s -1 , 3000s -1 The elastic moduli under strain rate conditions are 0.15 MPa, 0.18 MPa, 0.23 MPa, 0.33 MPa, and 0.45 MPa, respectively. The elastic modulus of the polyurethane foam cushioning material FIAM-PUF based on the FIAM factor prepared in Example 2 shows a significant strain rate enhancement effect, and the material has an adaptive adjustment function according to the external load rate.

[0109] Defoaming rate parameter (η): After standing at room temperature for 48 hours after molding, the apparent volume shrinkage of the FIAM-PUF foam, a polyurethane foam cushioning material based on the FIAM factor prepared in Example 2, was measured to be approximately 2.4%, which was significantly lower than the 38.9% of the uncorrected system, indicating that the process solved the defoaming interference problem and the material molding was stable.

[0110] Example 3

[0111] A method for preparing a polyurethane foam cushioning material based on FIAM factors, in parts by mass, comprises the following steps:

[0112] (1) Preparation of FIAM factor;

[0113] (2) Introduction and dispersion of FIAM factors;

[0114] (3) The A component of the polyurethane foam raw material is introduced, and after the foaming is completed, the polyurethane foam cushioning material based on the FIAM factor (FIAM-PUF) is obtained.

[0115] Furthermore, the specific steps of step (1) are as follows:

[0116] (11) Preparation of STG (shear thickening gel) precursor:

[0117] The boron-containing raw material and hydroxyl-terminated polydimethylsiloxane (PDMS) were mixed by hot melt and continuously stirred at 500 rpm to cause borate esterification reaction to generate a STG precursor with a polyborosiloxane network having a low degree of crosslinking, wherein:

[0118] The mass ratio of the added boron-containing raw material to the hydroxyl-terminated polydimethylsiloxane is 2:100;

[0119] (12) 30 parts of the STG precursor obtained in step (11) and 10 parts of a boron-oxygen coordination enhancer were added to 50 parts of dimethyl silicone oil, and then stirred at 150 rpm using a magnetic stirrer in a constant temperature water bath at 80°C for 3 hours to obtain an intermediate product;

[0120] (13) Nanoparticle enhancement

[0121] After the intermediate product obtained in step (12) is cooled to room temperature, nano-scale fumed silica is slowly added in small amounts and multiple times, and stirred at a high speed of 2000 rpm to form a stable high-viscosity FIAM factor.

[0122] Furthermore, the boron-containing raw material in step (11) is boric acid.

[0123] Furthermore, the reaction temperature of the borate esterification reaction in step (11) is 140° C., and the reaction time is 5 h.

[0124] Furthermore, the boron-oxygen coordination enhancer in step (12) is phenylboric acid.

[0125] Furthermore, the viscosity of the dimethyl silicone oil in step (12) is 20 cSt.

[0126] Furthermore, in step (13), the addition ratio of the nano-scale fumed silica is 5% based on the total mass of the intermediate product;

[0127] The particle size of the nano-scale fumed silica is 10 nm.

[0128] Furthermore, the specific steps of step (2) are as follows:

[0129] (21) The FIAM factor obtained in step (1) is added to 8 parts of the B component of the polyurethane foam raw material to form a FIAM-B component, wherein:

[0130] Based on the total mass of the B component of the polyurethane foam raw material, the FIAM factor is added in an amount of 2 wt%;

[0131] The B component of the polyurethane foam raw material is composed of polyether polyol and stabilizer, wherein:

[0132] The mass ratio of polyether polyol to stabilizer is 100:0.5;

[0133] (22) The FIAM-B component obtained in step (21) was stirred at a rate of 300 rpm for 30 minutes, and then proceeded to step (23);

[0134] (23) The FIAM-B component stirred in step (22) was subjected to ultrasonic dispersion treatment at room temperature at a power of 100 W for 60 minutes to obtain the FIAM-B component.

[0135] Furthermore, the stabilizer in step (21) is L-580 polymerized siloxane stabilizer.

[0136] Furthermore, the specific steps of step (3) are as follows:

[0137] (31) Add 10.2 parts of component A for generating polyurethane foam raw materials to the FIAM-B component obtained in step (2), mix quickly and stir quickly to obtain a mixture;

[0138] (32) The mixture obtained in step (31) is immediately injected into a mold for free foaming. After the foaming is completed, a polyurethane foam cushioning material (FIAM-PUF) based on the FIAM factor is obtained.

[0139] Furthermore, component A of the polyurethane foam raw material generated in step (31) is isocyanate.

[0140] Furthermore, the isocyanate is 4,4'-diphenylmethane diisocyanate (MDI).

[0141] Furthermore, in step (31), the stirring speed is 1000 rpm and the stirring time is 10 seconds.

[0142] Furthermore, in step (32), the foaming temperature is controlled at 25° C., and the foaming time is controlled at 60 seconds.

[0143] Example 4

[0144] A method for preparing a polyurethane foam cushioning material based on FIAM factors, in parts by mass, comprises the following steps:

[0145] (1) Preparation of FIAM factor;

[0146] (2) Introduction and dispersion of FIAM factors;

[0147] (3) The A component of the polyurethane foam raw material is introduced, and after the foaming is completed, the polyurethane foam cushioning material based on the FIAM factor (FIAM-PUF) is obtained.

[0148] Furthermore, the specific steps of step (1) are as follows:

[0149] (11) Preparation of STG (shear thickening gel) precursor:

[0150] The boron-containing raw material and hydroxyl-terminated polydimethylsiloxane (PDMS) were mixed by hot melt and continuously stirred at 800 rpm to cause borate esterification reaction to generate a STG precursor with a polyborosiloxane network having a low degree of crosslinking, wherein:

[0151] The mass ratio of the added boron-containing raw material to the hydroxyl-terminated polydimethylsiloxane is 6:100;

[0152] (12) 40 parts of the STG precursor obtained in step (11) and 15 parts of a boron-oxygen coordination enhancer were added to 50 parts of dimethyl silicone oil, and then stirred at 350 rpm using a magnetic stirrer in a constant temperature water bath at 95°C for 3 hours to obtain an intermediate product;

[0153] (13) Nanoparticle enhancement

[0154] After the intermediate product obtained in step (12) is cooled to room temperature, nano-scale fumed silica is slowly added in small amounts and multiple times, and stirred at 3000 rpm to form a stable high-viscosity FIAM factor.

[0155] Furthermore, the boron-containing raw material in step (11) is phenylboric acid.

[0156] Furthermore, the reaction temperature of the borate esterification reaction in step (11) is 150° C., and the reaction time is 4 h.

[0157] Furthermore, the boron-oxygen coordination enhancer in step (12) is diphenylboric acid;

[0158] Furthermore, the viscosity of the dimethyl silicone oil in step (12) is 100 cSt.

[0159] Furthermore, in step (13), the addition ratio of the nano-scale fumed silica is 20% based on the total mass of the intermediate product;

[0160] The particle size of the nano-scale fumed silica is 30 nm.

[0161] Furthermore, the specific steps of step (2) are as follows:

[0162] (21) The FIAM factor obtained in step (1) is added to 8 parts of the B component of the polyurethane foam raw material to form a FIAM-B component, wherein:

[0163] Based on the total mass of the B component of the polyurethane foam raw material, the FIAM factor is added in an amount of 10 wt %;

[0164] The B component of the polyurethane foam raw material is composed of polyether polyol and stabilizer, wherein:

[0165] The mass ratio of polyether polyol to stabilizer is 100:0.6;

[0166] (22) Stir the FIAM-B component obtained in step (21) at a rate of 500 rpm for 10 minutes, and then proceed to step (23);

[0167] (23) The FIAM-B component stirred in step (22) was subjected to ultrasonic dispersion treatment at room temperature at a power of 300 W for 20 minutes to obtain the FIAM-B component.

[0168] Furthermore, the stabilizer in step (21) is ethylene glycol monoallyl ether.

[0169] Furthermore, the specific steps of step (3) are as follows:

[0170] (31) Add 11.2 parts of component A for forming a polyurethane foam raw material to the FIAM-B component obtained in step (2), mix quickly and stir quickly to obtain a mixture;

[0171] (32) The mixture obtained in step (31) is immediately injected into a mold or placed in an open space for free foaming. After the foaming is completed, a polyurethane foam cushioning material (FIAM-PUF) based on the FIAM factor is obtained.

[0172] Furthermore, component A of the polyurethane foam raw material generated in step (31) is isocyanate.

[0173] Furthermore, the isocyanate is toluene diisocyanate (TDI).

[0174] Furthermore, in step (31), the stirring speed is 1500 rpm and the stirring time is 5 seconds.

[0175] Furthermore, in step (32), the foaming temperature is controlled at 60° C., and the foaming time is controlled at 10 seconds.

[0176] Example 5

[0177] A method for preparing a polyurethane foam cushioning material based on FIAM factors, in parts by mass, comprises the following steps:

[0178] (1) Preparation of FIAM factor;

[0179] (2) Introduction and dispersion of FIAM factors;

[0180] (3) The A component of the polyurethane foam raw material is introduced, and after the foaming is completed, the polyurethane foam cushioning material based on the FIAM factor (FIAM-PUF) is obtained.

[0181] Furthermore, the specific steps of step (1) are as follows:

[0182] (11) Preparation of STG (shear thickening gel) precursor:

[0183] The boron-containing raw material and hydroxyl-terminated polydimethylsiloxane (PDMS) were mixed by hot melt and continuously stirred at 600 rpm to cause borate esterification reaction to generate a STG precursor with a polyborosiloxane network having a low degree of crosslinking, wherein:

[0184] The mass ratio of the added boron-containing raw material to the hydroxyl-terminated polydimethylsiloxane is 4:100;

[0185] (12) 35 parts of the STG precursor obtained in step (11) and 12 parts of a boron-oxygen coordination enhancer were added to 50 parts of dimethyl silicone oil, and then stirred at 200 rpm in a constant temperature water bath at 85°C for 3.5 hours using a magnetic stirrer to obtain an intermediate product;

[0186] (13) Nanoparticle enhancement

[0187] After the intermediate product obtained in step (12) is cooled to room temperature, nano-scale fumed silica is slowly added in small amounts and multiple times, and stirred at a high speed of 2500 rpm to form a stable high-viscosity FIAM factor.

[0188] Furthermore, the boron-containing raw material in step (11) is diphenylboric acid. In other embodiments, the boron-containing raw material in step (11) is a mixture of boric acid, phenylboric acid and diphenylboric acid in equal mass ratios.

[0189] Furthermore, the reaction temperature of the borate esterification reaction in step (11) is 145° C., and the reaction time is 4.5 h.

[0190] Furthermore, the boron-oxygen coordination enhancer in step (12) is a mixture of phenylboric acid and diphenylboric acid in equal mass ratio.

[0191] Furthermore, the viscosity of the dimethyl silicone oil in step (12) is 60 cSt.

[0192] Furthermore, in step (13), the addition ratio of the nano-scale fumed silica is 10% based on the total mass of the intermediate product;

[0193] The particle size of the nano-scale fumed silica is 20 nm.

[0194] Furthermore, the specific steps of step (2) are as follows:

[0195] (21) The FIAM factor obtained in step (1) is added to 8 parts of the B component of the polyurethane foam raw material to form a FIAM-B component, wherein:

[0196] Based on the total mass of the B component of the polyurethane foam raw material, the FIAM factor is added in an amount of 4 wt%;

[0197] The B component of the polyurethane foam raw material is composed of polyether polyol and stabilizer, wherein:

[0198] The mass ratio of polyether polyol to stabilizer is 100:0.5;

[0199] (22) The FIAM-B component obtained in step (21) was stirred at a rate of 400 rpm for 15 minutes, and then proceeded to step (23);

[0200] (23) The FIAM-B component stirred in step (22) was subjected to ultrasonic dispersion treatment at room temperature at a power of 200 W for 30 minutes to obtain the FIAM-B component.

[0201] Furthermore, the stabilizer in step (21) is a mixture of L-580 polymerized siloxane stabilizer, methylcyclohexylamine and ethylene glycol monoallyl ether in equal weight ratios. In other embodiments, the stabilizer in step (21) is a mixture of methylcyclohexylamine and ethylene glycol monoallyl ether in equal weight ratios.

[0202] Furthermore, the specific steps of step (3) are as follows:

[0203] (31) Add 10.5 parts of component A for generating polyurethane foam raw materials to the FIAM-B component obtained in step (2), mix quickly and stir quickly to obtain a mixture;

[0204] (32) The mixture obtained in step (31) is immediately injected into a mold or placed in an open space for free foaming. After the foaming is completed, a polyurethane foam cushioning material (FIAM-PUF) based on the FIAM factor is obtained.

[0205] Furthermore, component A of the polyurethane foam raw material generated in step (31) is isocyanate.

[0206] Furthermore, the isocyanate is naphthalene diisocyanate. In another embodiment, the isocyanate is a mixture of 4,4'-diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), and naphthalene diisocyanate (NDI) in equal weight ratios.

[0207] In another embodiment, in step (21), the FIAM factor is added in an amount of 6 wt % based on the total mass of component B of the polyurethane foam raw material;

[0208] The amount of component A added in step (31) to generate the polyurethane foam raw material is 10.8 parts.

[0209] Furthermore, in step (31), the stirring speed is 1200 rpm and the stirring time is 8 seconds.

[0210] Furthermore, in step (32), the foaming temperature is controlled at 50° C., and the foaming time is controlled at 20 seconds.

[0211] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the above embodiments, and various modifications can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention.

Claims

1. A method for preparing a polyurethane foam cushioning material based on FIAM factors, characterized in that: Here are the steps: (1) Preparation of FIAM factor; (2) Introduction and dispersion of FIAM factors; (3) The A component of the polyurethane foam raw material is introduced, and after the foaming is completed, the polyurethane foam cushioning material based on the FIAM factor is obtained.

2. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 1, characterized in that: In parts by mass, the specific steps of step (1) are as follows: (11) Preparation of STG precursor: The boron-containing raw material and the hydroxyl-terminated polydimethylsiloxane are mixed by hot melt mixing and continuously stirred at a speed of at least 500 rpm to cause a borate esterification reaction to form an STG precursor having a polyborosiloxane network with a low degree of crosslinking, wherein: The mass ratio of the added boron-containing raw material to the hydroxyl-terminated polydimethylsiloxane is (2-6):100; (12) adding 30 to 40 parts of the STG precursor obtained in step (11) and 10 to 15 parts of a boron-oxygen coordination enhancer to 50 parts of dimethyl silicone oil, and then stirring the mixture in a water bath at a constant temperature of at least 80° C. using a magnetic stirrer at at least 150 rpm for at least 3 hours to obtain an intermediate product; (13) Nanoparticle enhancement After the intermediate product obtained in step (12) is cooled to room temperature, nano-scale fumed silica is slowly added in small amounts and multiple times, and stirred at a high speed of at least 2000 rpm to form a stable high-viscosity FIAM factor.

3. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 2, characterized in that: The boron-containing raw material in step (11) is one or more of boric acid, phenylboric acid, and diphenylboric acid, and / or The reaction temperature of the borate esterification reaction in step (11) is 140-150° C., the reaction time is 4-5 h, and / or The boron-oxygen coordination enhancer in step (12) is one or more of phenylboric acid, diphenylboric acid, and / or The viscosity of the dimethyl silicone oil in step (12) is 20 to 100 cSt, and / or In step (13), the addition ratio of the nano-scale fumed silica is 5% to 20% based on the total mass of the intermediate product; The particle size of the nano-scale fumed silica is 10 to 30 nm.

4. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 1, wherein: In parts by mass, the specific steps of step (2) are as follows: (21) The FIAM factor obtained in step (1) is added to 8 parts of the B component of the polyurethane foam raw material to form a FIAM-B component, wherein: Based on the total mass of the B component of the polyurethane foam raw material, the FIAM factor is added in an amount of 2 wt% to 10 wt%; The B component of the polyurethane foam raw material is composed of polyether polyol and stabilizer, and the mass ratio of the polyether polyol to the stabilizer is 100:(0.4-0.6); (22) Stirring the FIAM-B component obtained in step (21) at a rate of 300-500 rpm for at least 10 minutes, and then proceeding to step (23); (23) The FIAM-B component stirred in step (22) is subjected to ultrasonic dispersion treatment at room temperature at a power of 100 to 300 W for at least 20 minutes to obtain the FIAM-B component.

5. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 4, characterized in that: The stabilizer in step (21) is one or more of L-580 polymerized siloxane stabilizer, methylcyclohexylamine, and ethylene glycol monoallyl ether.

6. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 1, characterized in that: In parts by mass, the specific steps of step (3) are as follows: (31) adding an appropriate amount of component A for generating a polyurethane foam raw material to the FIAM-B component obtained in step (2), and rapidly mixing and stirring to obtain a mixture; (32) The mixture obtained in step (31) is immediately injected into a mold or placed in an open space for free foaming. After the foaming is completed, a polyurethane foam cushioning material based on the FIAM factor is obtained.

7. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 6, characterized in that: Component A of the polyurethane foam raw material generated in step (31) is isocyanate.

8. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 7, characterized in that: The isocyanate is one of 4,4'-diphenylmethane diisocyanate, toluene diisocyanate and naphthalene diisocyanate.

9. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 6, characterized in that: In step (31): If the addition ratio of the FIAM factor is 2 wt% to 4 wt%, the addition amount of component A for generating the polyurethane foam raw material in step (31) is 10.2 to 10.5 parts; If the addition ratio of the FIAM factor is 4 wt% to 6 wt%, the addition amount of component A for generating the polyurethane foam raw material in step (31) is 10.5 to 10.8 parts; If the addition ratio of the FIAM factor is 6 wt% to 10 wt%, the addition amount of component A for generating the polyurethane foam raw material in step (31) is 10.8 to 11.2 parts.

10. The method for preparing a polyurethane foam cushioning material based on FIAM factors according to claim 6, characterized in that: In step (31), the stirring speed is 1000-1500 rpm, the stirring time is 5-10 seconds, and / or In step (32), the foaming temperature is controlled at 25 to 60° C., and the foaming time is controlled at 10 to 60 seconds.